Gross anatomical and radiographic findings of museum preserved buffalo calves conjoined twin for learning purposes - Tolba, Ayman; Fargali, Haithem A; Mohamed Daghash, Samer (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: Current study aimed for documenting a rare case in buffalo calves in Egypt about embryogenesis anomalies followed by dystocia. Material and methods: The stillborn calf was preserved using Elnady technique. The twin was radio-graphed in ventrodorsal position and several digital images were taken due to large size of the twin and were stitched together using Adobe Photoshop. The preserved twin specimen was kept in a wooden glass cabinet at the Anatomy Museum, Faculty of Veterinary Medicine, Cairo University with a booklet described the case and a video CD for dystocia operation steps in cows and buffalos. Results: The external features of the twin were classified as dicephalus, tetrabrachius, Parapagus, and bipus. Radiographic study showed that the twin had two vertebral columns that converged at the lumbosacral region to come adjacent to each other with absence of sacrum and coccygeal vertebrae. The trunk cavities showed two sets of heart and lung, two stomachs; left one in the abdominal cavity and the right one in thoracic cavity. The two duodenum fused together to form one set of intestine terminated in persistent cloaca with the two ureters originated from the single set of two kidneys. It had one fused liver received the two umbilical veins and had two gall bladders. Conclusion: The present study recommended the preservation of rare specimens using Elnady technique for long term to facilitate student’s interaction with one of the rarest cases in buffalo that causes dystocia. J. Adv. Vet. Anim. Res., 7(1): 56-61, March 2020